2008
DOI: 10.3354/meps07254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal dynamics in a Zostera noltii meadow on phosphorus and iron cycles in a tidal mudflat (Arcachon Bay, France)

Abstract: A study was conducted in Arcachon Bay, France, to determine the effect of seasonal dynamics in a Zostera noltii meadow on P and Fe cycles in the superficial sediments of a tidal mudflat. The redox-sensitive Fe particulate pool and associated P in the root zone showed a seasonal variation following the growth and decay of Z. noltii biomass, with a maximum content during the growth period. In comparison, the bare sediments did not show significant seasonal changes. A dissolved inorganic phosphorus (DIP) uptake w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 48 publications
(85 reference statements)
5
22
0
Order By: Relevance
“…Many flooded or waterlogged plants show radial oxygen loss (ROL) from their roots, and the level and pattern of ROL is determined by photosynthetic rate, root architecture and root morphology (Armstrong, 1979; Jackson, 1985; McKee et al, 1988; Laan et al, 1991; Jackson and Armstrong, 1999; Visser et al, 2003; Frederiksen and Glud, 2006; Visser and Bögemann, 2006; Voesenek et al, 2006; Deborde et al, 2008). During nighttime, sulfide intrusion into roots and rhizomes is highest (Borum et al, 2005).…”
Section: Biological Protection: Radial Oxygen Loss From Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many flooded or waterlogged plants show radial oxygen loss (ROL) from their roots, and the level and pattern of ROL is determined by photosynthetic rate, root architecture and root morphology (Armstrong, 1979; Jackson, 1985; McKee et al, 1988; Laan et al, 1991; Jackson and Armstrong, 1999; Visser et al, 2003; Frederiksen and Glud, 2006; Visser and Bögemann, 2006; Voesenek et al, 2006; Deborde et al, 2008). During nighttime, sulfide intrusion into roots and rhizomes is highest (Borum et al, 2005).…”
Section: Biological Protection: Radial Oxygen Loss From Rootsmentioning
confidence: 99%
“…During nighttime, sulfide intrusion into roots and rhizomes is highest (Borum et al, 2005). Rhizosphere oxidation provides an obvious potential defense mechanism against the toxicity of reduced components such as sulfide (Pitts et al, 1972; Mendelssohn and McKee, 1988; Armstrong et al, 1996; Smolders and Roelofs, 1996; Hemminga, 1998; Armstrong and Armstrong, 2001, 2005; Holmer and Storkholm, 2001; Deborde et al, 2008), provided that soil aerobic microbial respiration and concomitant consumption of oxygen do not counteract this effect.…”
Section: Biological Protection: Radial Oxygen Loss From Rootsmentioning
confidence: 99%
“…A last parameter, the importance of riverine reactive Fe oxide deposition, has been invoked by Meiggs and Taillefert (2011) to explain a time series dataset in which salinity increases A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 without the simultaneous increase in sulphate reduction. Furthermore, numerous studies have described the seasonal variation of diagenesis intensity based on integrative indicators or on dissolved dataset only (Alperin et al, 1994;Beck et al, 2008;Cathalot et al, 2010;Dang et al, 2015;Deborde et al, 2008;Dellwig et al, 2007;Magni and Montani, 2006;Mortimer et al, 1999) and have also explained the observed temporal variability with the concept of steady state diagenesis, which varies with environmental parameters. However, on longer time scales, transient diagenesis is more often invoked.…”
Section: Introductionmentioning
confidence: 99%
“…Phanerogams convert nutrients from inorganic into particulate and dissolved organic forms, control phytoplankton growth, retain suspended matter, stabilise surface sediments and provide nursery areas for invertebrates and fish (Phillips & Menez 1988;Newman 1991;Caffrey & Kemp 1992;Blanchet et al 2004;Hasegawa et al 2008). Additionally, the radial oxygen loss from roots provides oxygen into anoxic sediments, which supports the reoxidation of reduced compounds (i.e., ammonium, methane and sulphides), the precipitation of soluble reactive phosphorus with ferric iron (Deborde et al 2008) and the removal of nitrogen via nitrification coupled denitrification (Reddy et al 1989;Caffrey & Kemp 1992;Ottosen et al 1999). Due to their overall importance, seagrasses have been studied in transitional brackish zones and coastal environments all around the world (Bortone 2000;Hemminga & Duarte 2000;Nielsen et al 2004).…”
Section: Introductionmentioning
confidence: 99%